2022
DOI: 10.1126/sciadv.abn0485
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 regulates the regenerative capacity of skeletal muscles via orchestration of stem cell morphological states

Abstract: Muscle stem cells (MuSCs) are essential for tissue homeostasis and regeneration, but the potential contribution of MuSC morphology to in vivo function remains unknown. Here, we demonstrate that quiescent MuSCs are morphologically heterogeneous and exhibit different patterns of cellular protrusions. We classified quiescent MuSCs into three functionally distinct stem cell states: responsive, intermediate, and sensory. We demonstrate that the shift between different stem cell states promotes regeneration and is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 69 publications
2
75
0
Order By: Relevance
“…Secondly, knocking out Piezo in Drosophila promotes axon regeneration 58 . Furthermore, Piezo1 negatively regulates the morphological activity (i.e., number of protrusions) of muscle stem cells 59 . Lastly, Piezo2 inhibits neurite outgrowth in N2A cells 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, knocking out Piezo in Drosophila promotes axon regeneration 58 . Furthermore, Piezo1 negatively regulates the morphological activity (i.e., number of protrusions) of muscle stem cells 59 . Lastly, Piezo2 inhibits neurite outgrowth in N2A cells 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Piezo2 inhibits neurite outgrowth in N2A cells 17 . In addition to membrane curvature, several parallel Piezo-related mechanisms can regulate the formation and growth of filopodia, including Ca 2+ signaling induced by the activation of Piezo and potential interactions between specific Piezo domains with cytoskeletal components 17 , 58 , 59 . Our data do not exclude these parallel mechanisms, rather, we suggest that the curvature preference of Piezo1 provides an additional route to control filopodia dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PIEZO1 plays a role in MuSC function. Ma et al (2022) demonstrated that MuSCs are morphologically heterogeneous with axon-like protrusions and that PIEZO1 is essential for preserving this feature, thereby priming MuSCs to be more responsive. In this study, we have revealed that Piezo1 deficiency affects the Rho activation ( Fig 7A–C ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, fetal acetylcholine receptors are re-expressed during regeneration throughout adult muscle [ 32 ], similar to what is seen in other niche systems. Structural maturation of fetal myofibers corresponds with changes to their plasma membrane, including expression of potassium-gated ion channels and calcium channels such as Piezo1 that regulate sarcolemma phospholipids and begin to assemble the components needed to build the SC niche [ 33 , 34 ]. Adult myofibers of the limb are made up of multiple myosins, which include MYH1 and MYH2 , unless they are undergoing regeneration, in which case they re-express embryonic and fetal myosin isoforms, such as what is seen in emerging niches in development.…”
Section: The Making Of the Stem Cell Niche In Skeletal Musclementioning
confidence: 99%
“…In one of the most devastating muscle-wasting diseases, Duchenne muscular dystrophy (DMD), SCs deficient in dystrophin lose polarity and are unable to appropriately form a niche, leading to a dysfunctional progenitor state, failed regeneration, and/or disease exacerbation [ 108 ]. Recent work has shown that SCs survey their niche via cell protrusions [ 109 ], which, when impaired, such as in Piezo1 knockout or DMD, primes SCs to activate from quiescence [ 33 ].…”
Section: Aging and Diseased Nichesmentioning
confidence: 99%